Big Sister Tells Me That I'm Black - Arnold Adoff; Lynch, Lorenzo, 1932- (U.S.A Holt, Rinehart and Winston, 1976)
A big sister helps her little black brother realize his identity.
Keywords: African Americans -- Juvenile poetry; Children's poetry, American; African Americans -- Poetry